Pengembangan Kawasan Wisata Mandeh melalui rekonstruksi kearifan lokal perempuan pesisir, Kabupaten Pesisir Selatan, Sumatera Barat - Siti Fatimah (Universitas Negeri Padang, 2022)
The Mandeh Tourism Area has been considered as Raja Ampat of the western Sumatra. However, this tourist area is very genuine and has not functioned as well as possible. In the National Tourism Development Master Plan (RIPPNAS) in 1998, the Mandeh tourism area recorded as a center for marine tourism development for the western region of Indonesia, along with Biak and Bunaken in the eastern part. Towards this preparation, exploring all aspects of local potential in preserving marine tourism is necessary. One of the aspects is through women's groups. Women's understanding is fundamental in environmental examination to create an environmentally friendly and women-friendly life. Therefore, investigating its potential as a reconstruction reference is necessary. This paper aims to describe the local potential of women in the Mandeh tourist area through the rebuilding of environmentally friendly local wisdom. This article employed an approach that focuses on the historical method, especially the oral history method. Data was collected through in-depth interviews and participant observation. The primary informants of this study were women in the Mandeh Integrated Tourism Area using the snowball technique. Data analysis was collected by using a historical analysis model. The local wisdom of Mandeh women can be categorized into several groups; (1) in preserving the environment and maintaining marine ecosystems through the prevention of their husbands who work as fishermen in brutal fishing; (2) utilization of the natural surroundings for healthy food and medicine; (3) culinary processing based on local potential.